On the role of Nb-related sites of an oxidized β-TiNb alloy surface in its interaction with osteoblast-like MG-63 cells - Jirka, Ivan; Vandrovcová, Marta; Frank, Otakar; Tolde, Zdeněk; Plšek, Jan; Luxbacher, Thomas; Bačáková, Lucie; Starý, Vladimír (Materials science & engineering. C, Materials for biological applications, 2013)
β-Stabilized titanium (Ti) alloys containing non-toxic elements, particularly niobium (Nb), are promising materials for the construction of bone implants. Their biocompatibility can be further increased by oxidation of their surface. Therefore, in this study, the adhesion, growth and viability of human osteoblast-like MG 63 cells in cultures on oxidized surfaces of a β-TiNb alloy were investigated and compared with the cell behavior on thermally oxidized Ti, i.e. a metal commonly used for constructing bone implants. Four experimental groups of samples were prepared: Ti or TiNb samples annealed to 600 °C for 60 min in a stream of dry air, and Ti and TiNb samples treated in Piranha solution prior to annealing. We found that on all TiNb-based samples, the cell population densities on days 1, 3 and 7 after seeding were higher than on the corresponding Ti-based samples. As revealed by XPS and Raman spectroscopy, and also by isoelectric point measurements, these results can be attributed to the presence of T-Nb2O5 oxide phase in the surface of the alloy sample, which decreased its negative zeta (ζ)-potential in comparison with zeta (ζ)-potential of the Ti sample at physiological pH. This effect was tentatively explained by the presence of positively charged defects acting as Lewis sites of the surface Nb2O5 phase. Piranha treatment slightly decreases the biocompatibility of the samples, which for the alloy samples may be explained by a decrease in the number of defective sites with this treatment. Thus, the presence of Nb and thermal oxidation of β-stabilized Ti alloys play a significant role in the increased biocompatibility of TiNb alloys.
Keywords: Surface oxide phase; fotoelektronová spektroskopie; Niobium; lidé; Surface acidity; Cell Adhesion; Cell Proliferation; niob; Ramanova spektroskopie; Static Electricity; Spectrum Analysis, Raman; Oxidation-Reduction; Cell Survival; Microscopy, Electron, Scanning; Alloys; Biocompatibility; počet buněk; slitiny; Humans; buněčná adheze; Cell Count; proliferace buněk; tvar buňky; β-TiNb alloy surface; Cell Shape; viabilita buněk; statická elektřina; osteoblasty; Osteoblast-like MG-63 cells; oxidace-redukce; Osteoblasts; mikroskopie elektronová rastrovací; Surface Properties; povrchové vlastnosti; Photoelectron Spectroscopy